Influence of sowing time and leaf cuttings on the seed yield and quality components of palak (Beta vulgaris var bengalensis) - SINGH, RAJINDER; BASSI, GEETA; SINGH, DILBAG (The Indian Journal of Agricultural Sciences, 2026)
A field study to assess the effects of sowing time and leaf cuttings on the yield and quality of palak (Beta vulgaris L. var bengalensis) seed was carried out at Vegetable Research Farm of Punjab Agricultural University, Ludhiana during 2009–10 and 2010–11. The experiment was laid out in a split plot design with sowing time as main plot and cuttings as sub- plot treatment. The results revealed that crop sown in October with one cutting had maximum seed yield (27.83 q/ha), 100 seed weight (1.4 g), germination (80.33%), seed vigour index-I and vigour index-II, which was statistically at par with two cuttings but significantly higher than the November sown crop. Late sown crop coupled with more cuttings though increased the number of branches/plant and total green leaf yield but the seed yield and quality in terms of germination, seedling dry weight and vigour indices I and II was considerably reduced due to less absorption and storage of photosynthates. Thus, the crop sown in October cut once or twice besides giving more green leaf yield produced maximum seed yield and better quality seed in palak.